Combined Use of the Hemi-Split Tibialis Anterior Muscle and Soleus Muscle Flap for Reconstruction After the Excision of a Recurrent Soft Tissue Sarcoma in the Lower Leg - Atomura, Daisuke; Osaki, Takeo; Sakakibara, Shunsuke (Curēus (Palo Alto, CA), 2024)
Reconstruction of large tissue defects following soft tissue sarcoma (STS) resection in the lower extremity presents a significant challenge for plastic surgeons. The optimal method should be selected from a wide array of techniques, depending on the size and location of the defect. Both pedicled and free flaps have demonstrated favorable outcomes. However, due to the nature of STS, there is concern about recurrence and the potential complications for secondary reconstruction. A 78-year-old male with leiomyosarcoma in the proximal third of the leg underwent wide excision and reconstruction using a pedicled medial gastrocnemius muscle flap. Local recurrence occurred at six months postoperatively, necessitating a second extended resection. This was followed by reconstruction using a hemi-split tibialis anterior muscle and hemi-split soleus muscle flaps, combined with a split-thickness skin graft. The postoperative course was uneventful, with complete survival of both the muscle flap and skin graft and no functional limitations in the lower extremity. The hemi-split tibialis anterior and soleus muscle flaps are considered valuable methods for reconstruction, preserving lower extremity function.